Hydrodynamic impact to the cell stress during single cell recovery - Mohd Noor, Anas; Norali, Ahmad Nasrul; Zakaria, Zulkarnay; Mohd Noor, Aishah; Hashim, Hairulazwan (ARQII Publication, 2019)
Cell overstressed in single-cell recovery process leads to cell mortality during the isolation process. A glass capillaries micropipette can be useful as a tool for picking up cell based on the positive displacement picking up method. However, when a negative pressure applies to the micropipette glass for picking a cell, it produces hydrodynamic pressure to the cell medium. This pressure condition, which proportional to the stress of the cell during the recovery process. In this work, we present a numerical analysis of shear stress on cell cytoplasm. Parameters such as micropipette diameter size, micropipette tip distance to the target cell, and negative pressure impact to the cell are analyzed. As a result, shear stress of cell cytoplasm increased by a short distance of cell to the micropipette tip during the initial picking up process. However, during the cell flowing inside the micropipette, the shear stress produced to the cell has no difference to the micropipette diameter. Therefore, this study could provide a benefit understanding of cell stress phenomena for many types of cells in single-cell recovery application by proper selection of micropipette diameter, suction pressure and the minimal cell distance to during the recovery process.